2022
DOI: 10.3390/ani12151895
|View full text |Cite
|
Sign up to set email alerts
|

Influence of External Thermal Conditions on Temperature–Humidity Parameters of Indoor Air in a Czech Dairy Farm during the Summer

Abstract: The aim of this article is to show the relationship between external thermal conditions and the quality of the indoor environment on a dairy farm during the summer. The measurements were carried out on a large dairy farm of Holstein cattle situated in the Czech Republic. The research included the measurement of the cowshed for 440 lactating cows, a milking parlor, a maternity cowshed, a cowshed for dry cows, 69 individual calf hutches, and three outdoor group shelters for calves. The results of the registratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…This consideration, although the number of sheds in our study was decidedly lower, also appears to be valid for Mugello where some sheds have sprayers and fans while others have none. The sheds construction materials also have their influence, concerning this a recent study conducted in the Czech Republic (Kic 2022 ) showed as older brick cowsheds, used after reconstruction and modernization in many cases, for housing certain groups of cows, such as dry cows, or before and after calving, have a better heat storage. This is reflected in a good attenuation of indoor air temperatures and a shift of the highest temperatures by several hours.…”
Section: Discussionmentioning
confidence: 99%
“…This consideration, although the number of sheds in our study was decidedly lower, also appears to be valid for Mugello where some sheds have sprayers and fans while others have none. The sheds construction materials also have their influence, concerning this a recent study conducted in the Czech Republic (Kic 2022 ) showed as older brick cowsheds, used after reconstruction and modernization in many cases, for housing certain groups of cows, such as dry cows, or before and after calving, have a better heat storage. This is reflected in a good attenuation of indoor air temperatures and a shift of the highest temperatures by several hours.…”
Section: Discussionmentioning
confidence: 99%
“…Metric (fiber length), morphological (skin thickness), and morphometric (fiber diameter) methods were used (4,12). The Temperature and Humidity Index (THI) was calculated according to the following formula: THI=0.8 x dry bulb temperature of the air + (relative humidity x (dry bulb temperature of the air -14.4)/100+46.4 (14). A statistical analysis of the skin thickness and coat characteristics (weight, length and diameter) traits was performed using commercial statistical program (Statistica 10.0, StatSoft Inc. Tulsa, OK, USA), based on a linear model that included the effect of the breed and season, and the interaction between breed and season.…”
Section: Methodsmentioning
confidence: 99%
“…While the natural sounds are related to the animals, mechanical ones come from devices installed inside the barn or periodically pass through the building or its surroundings. One example of a permanent noise source is mechanical ventilation, which depends on the structure of barns (Herbut and Angrecka, 2015;Kic, 2017Kic, , 2022. The selection of the type of fans and air mixers is based on technical specifications which determine, among others, the power, efficiency, and volume of the operating equipment.…”
Section: Sources and Intensity Of Sound In Cattle Barn/facilitiesmentioning
confidence: 99%